2011
DOI: 10.1007/s12562-011-0413-0
|View full text |Cite
|
Sign up to set email alerts
|

Recall bias in recreational summer flounder party boat trips and angler preferences to new approaches to bag and size limits

Abstract: Three innovative approaches to bag and size limits were evaluated in the recreational summer flounder Paralichthys dentatus fishery. Each approach was designed to reduce discard mortality while increasing angler satisfaction, yet still limiting recreational take within management goals. Each was compared to the 2006 legal bag and size limits on party boat trips from New Jersey and New York. Angler-specific catch data were collected during the trips, and anglers completed a questionnaire while sailing back to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…A fundamental aspect of the charter boat industry is the ability of captains and crew to demonstrate the value of a trip through both the quantity and quality of the catch . However, recreational angler surveys consistently rank catch and retention of fish below intangibles, such as freedom to fish and camaraderie (Ditton et al, 1978;Bochenek et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A fundamental aspect of the charter boat industry is the ability of captains and crew to demonstrate the value of a trip through both the quantity and quality of the catch . However, recreational angler surveys consistently rank catch and retention of fish below intangibles, such as freedom to fish and camaraderie (Ditton et al, 1978;Bochenek et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, in all of these surveys, discard numbers and the disposition of catch (live or dead) are entirely self-reported by fishermen. This reliance is problematic because recall bias can greatly reduce the accuracy and precision of discard estimates (Ditton et al, 1978;Hanson and Sauls, 2011;Bochenek et al, 2012;Donaldson et al 44 ). Uncertainty in estimates of biological parameters may increase the risk of fisheries exceeding annual quotas or decrease their value for assessment models (Patterson et al, 2001a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given there were over 9000 recreational fishers in the Marlborough Sounds before the 2008 ban (Batstone et al 2009) the number of blue cod discarded is concerning. It is worth noting that studies in other fisheries have found that fishers tended to display recall bias and overestimated their discards by 2.2-2.4 times (Bochenek et al 2012;Sullivan 2003);…”
Section: Discussionmentioning
confidence: 94%
“…Along with the reported number of blue cod discarded, two additional questions (fishing experience and knowledge of the suggested best practices) from the larger online survey were selected to examine whether the experimental groups differed in important ways. The two additional variables were chosen as both would likely influence the condition (and thus mortality) in which the fish were discarded, the number caught (Bartholomew and Bohnsack 2005;Cooke and Wilde 2007;Muoneke and Childress 1994) and recall bias concerning the amount of discards (Bochenek et al 2012). No significant differences were found between the three groups regarding average blue cod discards F(2,412) = 2.37, p = .09, Marlborough Sounds fishing experience F(2, 418) = 2.501, p = .08, and familiarity with the code of practice F(2, 418) = 2.86, p = .06.…”
Section: Current Practicesmentioning
confidence: 99%